Digitalization of Education in the Global Context - S. V. Barabanova; A. A. Kaybiyaynen; N. V. Kraysman (Moscow Polytechnic University, 2019)
The paper addresses the advanced topics of engineering education, including digitalization, which were discussed at the 21st International Conference on Interactive Collaborative Learning (ICL) and 47th IGIP International Conference on Engineering Pedagogy (IGIP) held on the Kos Island, Greece in September, 2018. The conference set out a wide range of problems relating to a new interactive educational technology, to developing online-, digital, and e-learning, to the visualization and gamification of education, to developing in engineers academic and applied competences, to implementing new education environments, etc. The Russian researchers' contribution to the development of engineering pedagogy was emphasized, including improving training of engineering university professors and holding the SYNERGY Engineering Education Research and Practice Network Conference in the leading technical universities of Russia.